Search for Trustful Leadership in Secondary Schools: Is Empowerment the Solution?. (November 2016) - Freire, Carla; Fernandes, António
The purpose of this study is to analyse how the access to structures of empowerment by teachers in primary and secondary education impacts on their trust of the headmaster of the school management board. Using the theoretical framework of empowerment and trust in the context of companies, one adapted the constructs of these scales to the reality of primary and secondary schools. A questionnaire was presented to 112 teachers in order to evaluate the impact of empowerment structures on their trust of the leader. The results obtained indicate that a context of empowering work is significantly predictive of trust in the school's headmaster. The teaching staff who realize that they have access to empowerment structures (power, resources, opportunities, support and information) and feel that they can exercise some influence on the organization of their workplace are in a better position to trust the headmaster. The results are discussed and the contributions of the study to theory and to school administration are presented.